2006
DOI: 10.1111/j.1365-2958.2006.05078.x
|View full text |Cite
|
Sign up to set email alerts
|

Poly(A)‐polymerase I links transcription with mRNA degradation via σS proteolysis

Abstract: SummaryBacteria rapidly adapt to changes in growth conditions through control of transcription and specific mRNA degradation. Interplay of both mechanisms must exist in order to achieve fine-tuned regulation of gene expression. Transcription of the Escherichia coli bolA gene is mediated by the RpoS/ σ σ σ σ S transcription factor in response to environmental signals. In this report it is shown that the mechanisms of bolA1p mRNA transcription and degradation are tightly connected at the onset of stationary phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 62 publications
(121 reference statements)
0
21
0
Order By: Relevance
“…in a synthetic medium or stationary growth phase, insufficient nutrients and energy might be supplied through the activity of some SdrP‐regulated gene products. It has been shown that polyadenylation of mRNA is possibly an important factor that promotes adaptation to slow growth conditions such as those under which the amount of nutrients is limited (Jasiecki and Wegrzyn, 2003; Santos et al ., 2006). Oxidative damage may occur to DNA and proteins in T. thermophilus , especially in the stationary phase, as observed in many bacteria (Bridges, 1993; Ballesteros et al ., 2001; Nyström, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…in a synthetic medium or stationary growth phase, insufficient nutrients and energy might be supplied through the activity of some SdrP‐regulated gene products. It has been shown that polyadenylation of mRNA is possibly an important factor that promotes adaptation to slow growth conditions such as those under which the amount of nutrients is limited (Jasiecki and Wegrzyn, 2003; Santos et al ., 2006). Oxidative damage may occur to DNA and proteins in T. thermophilus , especially in the stationary phase, as observed in many bacteria (Bridges, 1993; Ballesteros et al ., 2001; Nyström, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Santos et al (42) noted that in the absence of PAP I, RpoS levels were reduced by threefold in stationary-phase cells. They also demonstrated that the effect seen was posttranscriptional and specifically affected protein stability.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted as previously described. 7 Equal amounts of total RNA were blotted onto Hybond + membranes (GE) and fixed by UV light. An mreB DNA probe spanning the entire mreB orf was obtained by PCR using Taq polymerase (Roche) and the primers MreB1 (5′-attgacctgggtactgcg-3′) and MreB2 (5′-ctcttcgctgaacaggtc-5′) produced by STABVida.…”
Section: Bola Affects Mreb Expression Levelsmentioning
confidence: 99%
“…4 The expression of bolA is tightly controlled. [5][6][7] bolA increases biofilm formation 8 and modulates cell permeability; 9 in addition, it was demonstrated that bolA increases the expression of PBP5, PBP6 and ampC mRNA. 10,11 In this work, we analyzed the effect of BolA on cell growth and elongation using a set of specific antibiotics that induce known morphology alterations through the inhibition of PBPs.…”
mentioning
confidence: 97%